Analysis Of The Implementation Of The ASEAN Political Security Community Framework In The Philippines In Counter Terrorism Efforts - Melinda, Susan; Darmayadi, Andrias (Global Political Studies Journal, 2024)
This research aims to analyze the Philippines' failure in tackling terrorism based on the ASEAN Political-Security Community (APSC) Blueprint mechanism. This research uses a descriptive-qualitative approach to describe facts, characteristics of subjects and objects precisely, also uses data collection techniques through literature review by collecting secondary data. The results show that although the Philippines has ratified the ASEAN Convention on Counter Terrorism (ACCT) in 2010, it still relies on a militaristic approach in dealing with the Abu Sayyaf group in Mindanao, which is contrary to the APSC framework that emphasizes a comprehensive security approach. Moreover, based on adherence theory and constructivism paradigm, the Philippines shows its identity incompatibility with the ASEAN framework, as its priority on counterterrorism relies on a militaristic rather than comprehensive approach. Therefore, the case indicates ASEAN's ineffectiveness in ensuring the level of adherence of member states to implement the agreed regional counter-terrorism mechanism. Keywords — Adherence theory, APSC, Terrorism, the Philippines